Andrographolide contributes to the attenuation of cardiac hypertrophy by suppressing endoplasmic reticulum stress - Qingxin Tian; Jianlong Liu; Qin Chen; Mingxiao Zhang (Pharmaceutical Biology, 2023)
AbstractContext Andrographolide (Andr) is a bioactive Andr diterpenoid extracted from herbaceous Andrographis paniculata (Burm. F.) Wall. ex Nees (Acanthaceae). Andr can relieve cardiac dysfunction in mice by inhibiting the mitogen-activated protein kinases (MAPK) pathway.Objective This study investigates the efficacy and underlying mechanism of Andr on cardiac hypertrophy in mice.Materials and methods Male C57 mice (20–25 g, 6–8 weeks) were divided into four groups (n = 10 mice/group) as sham group (sham operation), transverse aortic constriction (TAC) model group, TAC + Andr 100 mg/kg group and TAC + Andr 200 mg/kg group. Andr groups were given intragastric administration of Andr (100 and 200 mg/kg) once a day for 14 consecutive days. An in vitro hypertrophy model was established by adding 1 μM of Ang II to H9c2 cells for 48 h induction.Results In TAC-mice, Andr improved echocardiographic indices [reduced LVESD (30.4% or 37.1%) and LVEDD (24.8% or 26.4%), increased EF (22.9% or 42.6%) and FS (25.4% or 52.2%)], reduced BNP (11.5% or 23.6%) and Ang II levels (10.3% or 32.8%), attenuates cardiac fibrosis and reduces cardiac cell apoptosis in TAC mice. In vitro, Andr attenuated cardiomyocyte hypertrophy and decreased the protein expression of GRP78 (67.8%), GRP94 (47.6%), p-PERK (44.9%) and CHOP (66.8%) in Ang-II-induced H9c2 cells and reversed after endoplasmic reticulum (ER) stress agonist Tunicamycin (TN) treatment.Discussion and conclusions Andr was found to be an anti-hypertrophic regulator, which could attenuate cardiac hypertrophy by suppressing ER stress. It may be a new therapeutic drug for cardiac hypertrophy.